Cut From the Same Cloth : American women of myth, legend, and tall tale - San Souci, Robert D.; Pinkney, J. Brian; Yolen, Jane. (New York : Puffin Books, 2000)
A collection of twenty stories about legendary American women, drawing from folktales, popular stories, and ballads.
78308
Keywords: Tales -- United States; Tall tales -- United States; Women -- United States -- Folklore; Fokelore -- United States; Tall tales; Women -- Folklore